Preparation of Mg2Ni Hydrogen Storage Alloy Materials by High Energy Ball Milling - Xusheng Liu; Lei Zhou; Wenhao Li; Shaopeng Wu; Qinglan Huang; Yankun Wang; Xiaolan Cai (Advances in Materials Science and Engineering)
In this paper, Mg2Ni hydrogen storage alloy powder was prepared by high-energy ball milling mechanical alloying method, and the influence of stirring shaft rotation speed, ball milling time, and different sizes of ball mills on the formation time, powder morphology, and crystal structure of Mg2Ni alloy during ball milling was studied. The results show that the Mg2Ni alloy was obtained by high-energy ball milling in this work, and the efficiency was increased by about 76% compared with the traditional ball milling method. In the case of higher rotational speed or larger blades, the time to generate Mg2Ni alloy can be advanced, the alloying process can be shortened, and Mg2Ni alloy with a particle size of less than 10 um can be obtained. However, after the ball milling reaches a certain time, the cold welding and crushing of the alloy powder reach a balance, and the particle size is basically unchanged. The hydrogen storage alloy was activated, the hydrogen storage PCT curve was detected, and the hydrogen absorption kinetic curve and the PCT curve were analyzed. After ball milling at 900/1100 rpm for 13 hours, a Mg2Ni alloy with a single composition, extremely low impurity content, and partially amorphous and nanocrystalline coexistence was obtained. Its mass hydrogen storage density also reached the theoretical value of 3.6 wt%.